2015
DOI: 10.1590/0037-8682-0040-2015
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological aspects of Toxoplasma gondii infection in riverside communities in the Southern Brazilian Amazon

Abstract: Introduction:Toxoplasma gondii infection is widely prevalent in humans and other animals worldwide. Information on the prevalence of T. gondii infection is scarce in some regions of Brazil, including riverside communities along the Amazon River basin. Methods: The prevalence of T. gondii in 231 people, aged 1-85 years, who were living in four riverside communities along the Purus River, Lábrea, State of Amazonas, Brazil, was determined. Antibodies against T. gondii were assayed using a commercial enzyme-linked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 20 publications
2
8
1
7
Order By: Relevance
“…Interestingly, the seroprevalence of anti-T. gondii antibodies in the present study was lower than other Brazilian neglected populations, such as 131/231 (56.7%) persons of riverside communities in the northern and 119/148 (80.4%) indigenous persons in the central-western region [53,54]. In São Paulo, similar results were found, with 110/339 (32.4%) seropositive children from a lowsocioeconomic community [55].…”
Section: Discussionsupporting
confidence: 75%
“…Interestingly, the seroprevalence of anti-T. gondii antibodies in the present study was lower than other Brazilian neglected populations, such as 131/231 (56.7%) persons of riverside communities in the northern and 119/148 (80.4%) indigenous persons in the central-western region [53,54]. In São Paulo, similar results were found, with 110/339 (32.4%) seropositive children from a lowsocioeconomic community [55].…”
Section: Discussionsupporting
confidence: 75%
“…A serological survey performed in the metropolitan area of the City of Belém (Pará state), involving 2.740 individuals showed that the seroprevalence of toxoplasmosis in the general population was approximately 78% (CARMO, 2011). In studies conducted in other urban or rural areas in the Brazilian Amazon the seroprevalence was lower than the Belém one, but still high (CAVALCANTE et al, 2006;FERREIRA et al, 2009;CARMO et al, 2010a;VITALIANO et al, 2015).…”
Section: Introductionmentioning
confidence: 94%
“…Na Região Amazônica brasileira, alguns estudos demonstraram que, por suas características ecoepidemiológicas, a prevalência da infecção é alta 13,14,15 e, ainda assim, surtos de toxoplasmose aguda têm ocorrido eventualmente. Em 2004, em Monte Dourado, no Estado do Pará, foi relatado um surto envolvendo 40 indivíduos com perfil clínico e sorológico compatível com a toxoplasmose aguda, cuja transmissão foi, provavelmente, por ingestão de alimentos e/ou a inalação de poeira contaminada com oocistos de T. gondii 16 .…”
Section: Introductionunclassified